?SCREENING OF DRUGS AGAINST MICltOSPORIDIA (Biological Sciences - PJSIR, 1995)
Thirteen drugs were tested againstNosema bombycis Naegeli in an in vitro system using Spodoptera frugiperda cellculturetoinvestigateantimicrosporidialactivities.Drugstestedwere:fumagillin,benzimidazole, pentostam, thim- erosal,ciprofloxacin, metronidazole,itraconazole,sulphadimidine,sulphapyridine,rimocidinsulphate,cerulenin, imi- docarb dipropionate andcompound 566C80 (atovaquone).Only fivedrugs namely,fumagillin, benzimidazole, pento- starn,ciprofloxacinandthimerosalshowedantimicrosporidialactivitywheninfectedcultureswereexposedtothedrug. Although thimerosal inhibiteddevelopmentof the microsporidiarelative tocontrols,but itdid not prevent an increase in the percentage of infected cells from the initial level. The other form drugs not only prevented further spread of infections between cells but also reduced the levelof infectionfrom the initial point.The minimum concentrations of the drugs which inhibited further spread of the parasite were: fumagillin at 5.0 ug/ml, benzimidazole at 250 ug/ml, pentostam at 2000 ug/rnl and ciprofloxacin at 250 ug/ml,